Formulation of Self Micro-Emulsifying Dry Powder of Zingiber officinale (Rhizome) and Its Effect on Hepatoprotective Activity in Mice Model (Bangladesh Pharmaceutical Journal, 2023)
Liver complication is a major concern in the world. Finding out a new way to combat various liver diseases is very much required. Ginger has been reported to have hepato-protective activity. Here we aimed to formulate an oil-based (self-micro emulsifying) powder to improve the hepatoprotective activity of dry powder of Zingiber officinale (Ginger). Four different formulations of self-microemulsifying dry powder were prepared by mixing with different excipients. The formulated powder was characterized for the angle of repose, Hausner ratio and compressibility index. The hepato-protective activity of the formulated powder was evaluated in vivo. All of the parameters tested for powder characterization showed a good response in terms of flow property and compressibility. Formulated powder exhibited a significant decrease (p